Physicall Quality and Nutrient Content of Corn Straw Silage with Different Fermentation Time - Ayu Sri Trisnadewi, Anak Agung; Oka Cakra, I Gusti Lanang; Belawa Yadnya, Tjokorda Gede (Journal of Food Security and Agriculture, 2020)
The study aimed to determine the acidity (pH), physicall quality, and nutrient content of corn straw silage with different time fermentation. The experiments use a completely randomized design (CRD) with four treatments and each treatment was repeated five times, so there are 20 experimental units. The fourth treatments are W1 = 14 days fermentation, W2 = 21 days fermentation, W3 = 28 days fermentation, and W4 = 35 days fermentation. The parameters observed in this study are the acidity, physical quality (fungus, texture, color, aroma) and the nutrient content (dry matter (DM), organic matter (OM), ether extract (EE), crude fiber (CF), crude protein (CP), ash). Results of the experiment showed that the acidity (pH) silage of corn straw silage tended to decrease with the increasing of period fermentation, whereas from the physical of quality: fungus belonging to good criteria; texture, color, and aroma showed good medium values??and showed no significant difference with increasing of fermentation period. There was no significant difference in organic matter, crude fiber, and crude protein until 5 weeks of fermentation period, whereas there was a significant difference in dry matter, crude fat, NFE, and TDN from 21-35 days fermentation. It can be concluded that physically of quality and nutrient content are not significantly different.